« L’attention littéraire » dans les textes d’Alessandro Mendini (1931-2019) : une traduction permanente vers le projet - Catherine Geel (Appareil)
Alessandro Mendini belongs to a classical tradition, found among Italian designers and architects, where writing is a recognized and important activity, often on the side of theory. Author of more than 500 texts, 120 of them were translated into French between 2009 and 2014. It is thus the act of translation that allows Alessandro Mendini to shed light on the construction of a written and projective work where “attention to the literary” is what it is all about. The designer’s written matter, complex and ultimately highly organised, is not content to explain the man or the work, it is the very matter of his design work: the text goes beyond the unveiling of his main theoretical concepts of “sentimental robot”, “cynical man”, “decorative man”, and “natural object body”. Without lingering on these concepts which were the subject of introductions to the texts of the work Alessandro Mendini. Écrits. Architecture, design et projet (2014), we will decipher in this article 5 ways in which the designer connects his textual practice, beyond personal reflections, to a literary and artistic tradition: origin, foundation or connection of the project through the particularity of the objects he chooses. With the fragment, the place of the archive, writing as an art of living, the question of signs, it is this literary consistency that allows the formulation of a famous “object” that its author defines as theoretical: Proust’s Armchair. Here translation, beyond the activity necessary to the understanding of the projectual work, takes on two other interests: it obliges the designer’s intellectual archaeology, it is documented and “topographical” research and allows us to grasp how Alessandro Mendini theorizes in design the perceptive effects based on observations linked to the literary. Text and “translation” are for him a central subject, a gesture, an origin and a project process.